Limit Temperature State of Permafrost Earth-Fill Dam and Reservoir Floor (Predelnoye Temperaturnoye Sostoyaniye Merzloy Zemlyanoy Plotiny i Lozha Vodokhranilishcha) - Kuznetsov,G I (1977)
Dam-building and reservoir formation have a substantial influence on the natural temperature mode of permafrost soils that comprise the floor of a reservoir. These alterations are most strongly manifested in permafrost type dams within the upper thaw zone, particularly during the first years following the filling of the reservoir. The calculated limit temperature state of the base sets in after many years of temperature changes. During the operation of a freezing system permafrost dam stability is determined on the basis of the following factors: (1) boundary and size of the thaw zone located within the top wedge of the dam; (2) outline, size and temperature field of the permafrost zone, including the central part of the profile (permafrost core) and the entire lower wedge, and also the surrounding part of the upper wedge, which behaves as an insulation liner; (3) temperature-dependent strength, and water-resistant properties of the soils that make up the permafrost zone; (4) elimination of all local manifestations of natural filtration in closed thaw zones before the filling of the reservoir. This report discusses these factors in some detail. (Author) Trans. of Problemy Severnogo Stroitelstva n2 p50-73 1972.